Recent advances in TiO2/ZnS-based binary and ternary photocatalysts for the degradation of organic pollutants - Devagi, Kanakaraju; Aneshaa, Chandrasekaran (Elsevier B.V., 2023)
Semiconductor-mediated photocatalysis plays a pivotal role in the elimination of organic pollutants from water systems. Titanium dioxide (TiO2) and zinc sulphide (ZnS) semiconductors are commonly utilized as photocatalysts in water purification due to their physical and chemical stability and also large band gap. The drawbacks of both semiconductors,nevertheless, prevent them from being used in real and large-scale treatments. Therefore, binary and ternary-based TiO2/ZnS nanostructured materials may be a promising solution to improve the quantum efficiency, structural, and electrical features of pure TiO2 and ZnS semiconductors for improved photoefficiency. This review aims to unravel the development of binary TiO2/ZnS and the modification of ternary photocatalysts (TiO2/ZnS-X, X =metal, non-metal, and dye sensitization) by various approaches. The engineered TiO2/ZnS-based ternary nanostructured materials have exhibited exceptional performance to accelerate the degradation of organic pollutants in wastewater.These materials were fabricated by modifying TiO2/ZnS binary composite and embedding co-catalysts like carbonaceous material, polymeric material, transition metal, metal oxide, and metal. The relationship between the properties of the resulting nanomaterials and their photocatalytic performances has been examined. This review has also placed a special focus on the synthetic routes applied to derive the binary and ternary TiO2/ZnS composites. Another aim of this review is to scrutinize the factors that influence the performance of binary and ternary-based TiO2/ZnS composites on the degradation of organic pollutants. Opportunities for further investigation have been also outlined, along with limitations and impediments based on the current findings.